Inexact SA Method for Constrained Stochastic Convex SDP and Application in Chinese Stock Market. (23rd January 2018) - Chen, Shuang; Pang, Li-Ping; Lv, Jian; Xia, Zun-Quan
Abstract : We propose stochastic convex semidefinite programs (SCSDPs) to handle uncertain data in applications. For these models, we design an efficient inexact stochastic approximation (SA) method and prove the convergence, complexity, and robust treatment of the algorithm. We apply the inexact method for solving SCSDPs where the subproblem in each iteration is only solved approximately and show that it enjoys the similar iteration complexity as the exact counterpart if the subproblems are progressively solved to sufficient accuracy. Numerical experiments show that the method we proposed was effective for uncertain problem.